2021
DOI: 10.3389/fendo.2021.683297
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Exposure to Per- and Poly-Fluorinated Alkyl Substances and Growth, Adiposity, and Puberty in Children: A Systematic Review

Abstract: Per- or polyfluoroalkyl substances (PFAS), a family of synthetic polyfluorinated compounds, are widely used in consumer products. Ubiquitous exposures to PFAS, in consideration of their persistence, bioaccumulation potential, and toxicities have led to concerns regarding possible harmful effects during critical periods of development in early-life and long-term consequences on health. The potential effects of PFAS depend on various factors including the type of PFAS and the timing and level of exposure. We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 138 publications
(310 reference statements)
0
32
0
Order By: Relevance
“… 44 These results need to be confirmed because the role of these compounds as complex mixtures remains largely unknown. 45 …”
Section: Resultsmentioning
confidence: 99%
“… 44 These results need to be confirmed because the role of these compounds as complex mixtures remains largely unknown. 45 …”
Section: Resultsmentioning
confidence: 99%
“…For other types of PFAS and other growth measures besides weight, the evidence was very limited and more inconclusive as reviewed by Lee et al. ( Lee et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…PFAS can transfer across the placenta during pregnancy (Eryasa et al 2019;Wang et al 2019), making them a potential threat to fetuses during the most sensitive early stages of life. Previous epidemiological studies have suggested that prenatal PFAS exposures, mainly PFOS and PFOA, may be associated with decreased birth weight (Chen et al 2021;Gyllenhammar et al 2018;Lee et al 2021;Liew et al 2018;Maisonet et al 2012;Marks et al 2019;Meng et al 2018;Starling et al 2017) and increased risk of childhood overweight or adiposity (Braun et al 2016;Chen et al 2017Chen et al , 2019Gyllenhammar et al 2018;Lee et al 2021;Maisonet et al 2012;Starling et al 2019). However, several inconsistent results have also been reported, such as inverse or null associations for childhood growth (Andersen et al 2013;Barry et al 2014;Shoaff et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations